Potensi Ekstrak Rimpang Kencur (Kaempferia galanga L.) Menghambat Pertumbuhan Candida albicans - Annisa Rahmi; Erpan Roebiakto; Leka Lutpiatina (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2016)
Candida albicans infection is the cause of candidiasis. Candidiasis treatment can be done with a variety of antifungal drugs, one of them is rhizome of kencur (Kaempferia galanga L.). The Rhizome of kencur is selected as a traditional medicine because it contains chemical compounds such as flavonoids, tannins, saponins and essential oil that serves as an antifungal. This study aimed to determine the minimal inhibitory and minimal killing power and also an influence of kencur rhizome extract on the growth of Candida albicans in vitro. This research was true experimental design with posttest only control group design with tube dilution method. Results of Minimal Inhibitory Concentrations (MICs) research showed there was no clarity at concentration of 20 mg/mL, 30 mg/mL, 40 mg/mL, and it shows clarity at concentration of 50 mg/mL and 60 mg/mL. Results of Minimum Bactericidal Concentrations (MBCs) showed the number of colonies at concentration of 20 mg/mL were 84 colonies, concentration of 30 mg/mL were 48 colonies, concentration of 40 mg/mL were 27 colonies, concentration of mg/mL were 12 colonies and concentration of 60 mg/mL were 0 colony. Based on linear regression test, the result showed significance value of 0.000